The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00701-020-04384-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome, in-hospital healthcare consumption and in-hospital costs for hospitalised traumatic brain injury patients: a Dutch prospective multicentre study

Abstract: Background The high occurrence and acute and chronic sequelae of traumatic brain injury (TBI) cause major healthcare and socioeconomic challenges. This study aimed to describe outcome, in-hospital healthcare consumption and in-hospital costs of patients with TBI. Methods We used data from hospitalised TBI patients that were included in the prospective observational CENTER-TBI study in three Dutch Level I Trauma Centres from 2015 to 2017. Clinical data was completed with data on in-hospital healthcare consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 80 publications
(120 reference statements)
0
15
0
Order By: Relevance
“…Outcome is presented using the Glasgow Outcome Scale Extended (GOSE) extracted from routine follow-up consultations at 3 months (which include a neurological examination, as well as a description of current occupation including the percentage of working capability). A dichotomized GOSE in favorable (GOSE 5-8) and unfavorable (GOSE 1 to 4) was considered in the analysis, as in previous studies [5,32]. Furthermore, we analyzed separately patients who died (GOSE 1) and survivors.…”
Section: Data Collectionmentioning
confidence: 99%
“…Outcome is presented using the Glasgow Outcome Scale Extended (GOSE) extracted from routine follow-up consultations at 3 months (which include a neurological examination, as well as a description of current occupation including the percentage of working capability). A dichotomized GOSE in favorable (GOSE 5-8) and unfavorable (GOSE 1 to 4) was considered in the analysis, as in previous studies [5,32]. Furthermore, we analyzed separately patients who died (GOSE 1) and survivors.…”
Section: Data Collectionmentioning
confidence: 99%
“…The clinical trajectory of recovery after traumatic brain injuries can be unpredictable. Some patients arriving with moderate neurologic perturbations may deteriorate while others may improve and be discharged directly home [8,9,15]. Increased evidence about which interventions for these patients have a meaningful impact on outcomes is critical to improve care.…”
Section: Discussionmentioning
confidence: 99%
“…This study reported utility values specific to the clinical outcomes following TBI, based on the Glasgow Outcome Scale (GOS). We combined these utility values with GOS outcomes reported 6 months post-injury in a study of patients hospitalised with mild TBI (of all ages) [ 26 ]. The mean utility for all mild TBI patients was estimated at 0.796 for those surviving post-TBI, which was equal for both treatment groups.…”
Section: Methodsmentioning
confidence: 99%